Analisis Akses Informasi Kesehatan Dalam Memperoleh Pelayanan Kesehatan TB Paru Di Puskesmas Ngoresan, Jebres, Kota Surakarta - Oliva Virvizat Prasastin; Frieda Ani Noor (Universitas Duta Bangsa Surakarta, 2021)
Background: Incidence case of Tuberculosis (TB) still ranks first in the classification of infectious diseases at several health centers in Surakarta for the last 4 years. Meanwhile, in the last 4 years, efforts have been made to improve pulmonary TB health services, starting from case detection, access to services and treatment. The health centers that have the highest cases of pulmonary TB disease in Surakarta over the last 5 years include the Ngoresan Health Center (2018), Sangkrah Health Center (2017), Pajang Health Center (2016) and Banyuanyar Health Center (2015). Objectives: This study aims to analyze access of health information related to health services obtained by patients with pulmonary TB at Ngoresan Health Center, Jebres, Surakarta City. Methods: This research method uses a cross-sectional research design by filling out questionnaires on a research sample of 30 respondents. Result: Factors related to access of health information to obtaining Pulmonary TB Health Services at Ngoresan Health Center, Jebres Surakarta City are availability of health information, communication with health workers, transportation, family support and knowledge. Conclusion: the availability of health information, communication with health workers, transportation, family support and knowledge are affected by access of health information to obtaining pulmonary TB health services at Ngoresan Health Center, Jebres, Surakarta City.